Regional workshop on agrochemical use and mitigation - Putthana, V.; Unger, Fred (International Livestock Research Institute, 2024)
The responsible use of agrochemicals remains a pressing challenge in the ASEAN region, requiring a delicate balance between ensuring food security and agricultural productivity while safeguarding environmental sustainability and human health. On October 31, 2024, a pivotal step was taken to tackle this issue at the Regional Workshop on Agrochemical Use and Mitigation, held in Vientiane, Laos. Organized under the ASEAN CGIAR Innovate for Food Regional Program, the workshop was part of Intervention Package 1 (IP1), which focuses on regenerative agriculture, aquaculture, and sustainable agrochemical practices. The workshop convened 35 experts from a wide range of fields, including academia, government agencies, CGIAR centers, NGOs, and the private sector. Participants from Laos, Vietnam, Cambodia, and Thailand—representing the Greater Mekong Subregion (GMS)—came together to address the multifaceted challenges of agrochemical use in the region. The discussions focused on three key objectives: (i) analyzing agrochemical use across the livestock, crop, and aquaculture sectors, (ii) fostering cross-sectoral and cross-country exchanges within the GMS, and (iii) identifying and deliberating on potential mitigation strategies. The event was jointly organized by the Faculty of Agriculture at the National University of Laos (NUOL) and the International Livestock Research Institute (ILRI), highlighting the vital role of partnerships in tackling regional agricultural challenges. This workshop was both timely and critical, as the ASEAN region strives to meet the United Nations Sustainable Development Goals by 2030. The region faces a complex web of challenges, including climate change, rapid urbanization, biodiversity loss, water scarcity, poverty, food safety concerns (such as antimicrobial resistance), nutrition deficiencies, and social inequality. Tackling these interconnected issues demands a collaborative and holistic approach—a goal this workshop sought to advance. By uniting experts from diverse fields and countries, the workshop provided a valuable platform for exchanging ideas, sharing best practices, and developing innovative solutions. The insights and outcomes from this event are anticipated to shape policy decisions, inform research priorities, and foster collaborative initiatives aimed at advancing sustainable and responsible agrochemical use across the ASEAN region. This report offers a detailed account of the workshop proceedings, key insights, and actionable recommendations that emerged from the discussions. It serves as an essential resource for policymakers, researchers, and practitioners committed to advancing sustainable agricultural practices in the ASEAN region and beyond. The workshop was organized as part of Intervention Package 1 (IP1) under the ASEAN CGIAR Innovate for Food Regional Program. IP1 focuses on promoting regenerative agriculture practices and reducing the use of harmful agrochemicals in ASEAN Member States (AMS).